PENGUKURAN TINGKAT KAPABILITAS PADA PT SENTRAL ELECTRIC MENGGUNAKAN FRAMEWORK COBIT 5 - Widjaja, Michael; Setiawan, Johan (APPS Publications, 2022)
ABSTRACT Objective – to determine the company capabilities based on COBIT 5 framework and provide recommendation that can be used to improve the company capabilities per COBIT 5 Standard. Methodology – The research uses qualitative method by conducting interviews and do observation on the company daily operation of the related department at PT Sentral Electric. Findings – The research found that the capabilities of PT Sentral Electric in domain APO07, BAI09, EDM 01, MEA01, and DSS03 can only reach level 1. The study also found that the company had several shortcomings that caused some related activities to need improvement. Novelty – The research uses gap analysis to find the shortcomings and find the gap. The company thus can make improvements by implementing the given recommendation. Keywords – assessment, COBIT 5, Framework, PT.sentral Elektrik